EVALUATION OF OPTICAL AND ELECTROPHYSICAL PARAMETERS OF OXIDE THIN FILMS DEPOSITED ON DIELECTRIC SUBSTRATES (Global Conference on Multidisciplinary Research and Innovation, 2026)
Oxide semiconductor thin films have become highly important materials in modern electronics, optoelectronics, and renewable energy technologies due to their unique optical and electrophysical properties. ZnO, CuO, and Cu₂O thin films exhibit considerable potential for application in photovoltaic systems, transparent conductive coatings, photodetectors, and sensor devices. The functional characteristics of these materials strongly depend on their structural organization, optical behavior, and electrical transport properties.The present study investigates the optical and electrophysical parameters of oxide semiconductor thin films deposited on dielectric substrates using ion-plasma technology. Particular attention was devoted to the relationship between structural characteristics, optical absorption behavior, and electrical conductivity of the synthesized films.The obtained results demonstrated that deposition conditions significantly influence optical transparency, absorption coefficient, electrical resistivity, and charge transport characteristics of oxide semiconductor layers. ZnO thin films exhibited high optical transparency and stable conductivity, while CuO and Cu₂O films demonstrated strong optical absorption within the visible spectral region.The investigated oxide thin films showed favorable electrophysical and optical characteristics suitable for application in optoelectronic systems and renewable energy technologies. The obtained results confirm that ion-plasma deposition provides effective control over the functional parameters of semiconductor oxide films.
Keywords: Oxide thin films, optical properties, electrophysical characteristics, ZnO, CuO, Cu₂O, ion-plasma deposition, semiconductor materials.